Production process of composite water purifying agent polyaluminum ferric sulfate
By optimizing the preparation process of polymerized aluminum sulfate iron, the problem of difficulty controlling parameters in the preparation process has been solved, the turbidity removal rate and stability of the product are improved, and their application scope is expanded.
Patent Information
- Application Number
- CN202411549342.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-28
AI Technical Summary
During the preparation process of polymeric ferrous aluminum sulfate, it is difficult to accurately control key preparation parameters, such as the roasting temperature, the amount and concentration of sulfuric acid, the reaction time and temperature, etc., which makes it difficult to optimize the preparation process conditions, and traditional composite water purifiers are reducing the water body The performance is poor in turbidity and the scope of application is limited.
The production process of a composite water puriter polymerized aluminum sulfate, including the analysis and pre -treatment of the composition of high -speed rail aluminum ore, the steps such as roasting, soluble sulfuric acid, hydrolyzed polymerization, etc. Optimize the preparation process conditions such as reaction time and temperature.
The ideal process conditions of polymerized aluminum sulfate iron are realized, the turbidity removal rate of the product is improved, the preparation cost is reduced, and the stability and applicability of the product are enhanced.
Smart Images

Figure CN119370898A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water purifier preparation, and in particular to a production process of composite water purifier polyaluminium ferric sulfate. Background Art
[0002] With the rapid development of industry, agriculture and economy, water pollution is becoming more and more serious, and sewage treatment is receiving more and more attention. As a result, many water treatment methods such as biological treatment, chemical oxidation, electrodialysis, ion exchange, adsorption, flocculation and sedimentation have emerged. Considering the economic applicability and safe use, flocculation and sedimentation is currently the most widely used, most applicable and low-cost method in water treatment. The selection of flocculants is the key to this method. After adding flocculants to sewage, solid-liquid separation is achieved through contact with suspended matter and colloidal particles in the water, thereby reducing the turbidity, chromaticity, COD and other indicators of the raw water. With the continuous development and growth of water treatment agents and the requirements of treatment systems for effluent, the development and utilization of new and efficient flocculants are receiving more and more attention. Polyaluminium ferric sulfate is a more practical composite water purifier.
[0003] In the current preparation process of polyaluminum ferric sulfate, it is difficult to accurately control key preparation parameters, such as roasting temperature, amount and concentration of sulfuric acid, reaction time and temperature, etc. This makes it difficult to optimize the ideal process conditions for preparing flocculant polyaluminum ferric sulfate through sulfuric acid dissolution method. In addition, traditional composite water purifiers perform poorly in reducing water turbidity, and their application scope is therefore limited.
[0004] Currently, no effective solution has been proposed for the problems in the related technologies. Summary of the invention
[0005] In order to overcome the above problems, the present invention aims to propose a production process of a composite water purifier polyaluminum ferric sulfate, with the aim of solving the problem that it is difficult to accurately control key preparation parameters in the current preparation process of polyaluminum ferric sulfate, such as roasting temperature, amount and concentration of sulfuric acid used, reaction time and temperature, etc., which makes it difficult to optimize the ideal process conditions for preparing the flocculant polyaluminum ferric sulfate by sulfuric acid acid dissolution method. In addition, traditional composite water purifiers perform poorly in reducing water turbidity, and their application scope is therefore limited.
[0006] To this end, the specific technical solution adopted by the present invention is as follows:
[0007] A production process of composite water purifier polyaluminium ferric sulfate, the production process comprising the following steps:
[0008] Step 1: Analyze and pre-treat the composition of the raw material high-iron bauxite;
[0009] Step 2: Weigh a certain amount of high-iron bauxite and roast it in a high-temperature furnace for 2 hours;
[0010] Step 3: put the roasted high-iron bauxite into a container, add sulfuric acid in an amount according to the theoretical ratio of sulfuric acid dosage to raw material, add the sulfuric acid all at once and stir thoroughly;
[0011] Step 4: placing the obtained intermediate product in a 60°C-140°C glycerol oil bath, heating and acid dissolving, adding a certain amount of catalyst and alkalizing agent for hydrolysis and polymerization for a period of time after acid dissolution;
[0012] Step 5: Turn off the oil bath, take out the container, cool and ripen to obtain the product, and measure the product.
[0013] Optionally, the analysis of the composition of the raw material high-iron bauxite in step one includes determination of iron oxide content, determination of aluminum oxide content, calculation of effective ingredient content and determination of basicity.
[0014] Optionally, the analysis of the composition of the raw material high-iron bauxite comprises the following steps:
[0015] S1. Determination of iron oxide content: the determination method adopts mercury-free iron determination method, and the calculation formula of iron oxide content is:
[0016] In the formula, V represents the volume value of K2Cr2O7 standard titration solution consumed during titration, C represents the accurate value of the concentration of K2Cr2O7 standard titration solution, m represents the mass of the sample, and M represents the molar mass of Fe2O3;
[0017] S2. Determination of alumina content. The calculation formula of alumina content expressed as mass fraction is:
[0018] Where V0 represents the blank test consumption Z n The volume of Cl2 standard titration solution, V represents the volume consumed by the sample n The volume of Cl2 standard titration solution, C represents Z n The concentration of the Cl2 standard titration solution, m is the mass of the sample, and M is the value of the molar mass of Al2O3;
[0019] S3. Calculation of active ingredient content: X3 = X2 + 0.6348 × X1.
[0020] In the formula, X1 is the measured Fe2O3 content, X2 is the measured Al2O3 content, and 0.6348 is the coefficient for converting Fe2O3 into Al2O3;
[0021] S4. Determination of basicity. The basicity is calculated as a percentage. The calculation formula is:
[0022] Wherein, V0 is the volume of NaOH standard solution consumed in the blank test, V is the volume of NaOH standard solution consumed in the test sample, C is the concentration of NaOH standard solution, m is the mass of the sample, and M is [OH - ] is the value of the molar mass, X3 is the measured effective component content, 0.5293 is the coefficient for converting Al2O3 into Al, and 8.994 is The molar mass of .
[0023] Optionally, the high-iron bauxite weighed in step 2 is 20 g, and the roasting temperatures are 500°C, 600°C, 700°C, 800°C and 900°C.
[0024] Optionally, the step 1 pretreatment includes a coagulation process, and the specific steps of the coagulation process are:
[0025] A1. Simulate wastewater preparation, weigh a certain amount of kaolin, dissolve it in water, measure the turbidity of the raw water, and control its turbidity at around 340NTU;
[0026] A2. Coagulation: Take 400 ml of the experimental water sample and add 1% polyaluminium ferric sulfate flocculant. Use a program-controlled coagulation experimental agitator to conduct the experiment. Set the agitator to 300 r / min for each program. -1 Rapid stirring for 30s, 150r·min -1 Stir for 5min, 70r·min -1 Stir slowly for 10 minutes, turn off the six-joint mixer, and then let it settle for 10 minutes. Take the upper clear liquid and immediately measure the residual turbidity of the effluent.
[0027] A3. Characterization of analysis results, turbidity removal rate calculation formula:
[0028] Where T0 is the raw water turbidity, and T is the residual turbidity of the coagulated effluent.
[0029] Optionally, the product determination in step 5 includes determining the morphology of polyaluminium ferric sulfate, the monomer state [Al+Fe] content M a Calculation: Polymeric [Al+Fe] content M b Calculation: Gel state [Al+Fe] content M c Calculation of: M c (%) = 100% - M a -M b ,
[0030] Among them, OD0 is the absorbance value of the blank sample after boiling, OD1 is the absorbance value of the sample for 1 minute, and OD 240 OD- is the absorbance value of the sample corresponding to 240 min, and OD- is the absorbance value of the sample after boiling.
[0031] Optionally, the determination of the product in step five also includes scanning electron microscopy analysis, specifically, dissolving a certain amount of high-iron bauxite raw material and flocculant product in ethanol solution, breaking them up evenly by ultrasound, and then dropping them on aluminum foil. After drying, sticking it on a sample holder, and then spraying the sample with gold, and then observing it with a scanning electron microscope.
[0032] Optionally, in step 3, the amount of sulfuric acid added is 0.8:1, 1:1, 1.2:1, 1.4:1 and 1.6:1, and the concentration of sulfuric acid is 5 mol·L -1 , 7mol·L -1 , 9mol·L -1 , 11 mol·L -1 and 13 mol·L -1 , and determine the effect of different sulfuric acid concentrations on turbidity removal rate.
[0033] Optionally, the hydrolysis polymerization reaction time in step 4 is 60 min, 75 min, 90 min, 105 min, 120 min and 135 min, respectively, and the effects of different times on the hydrolysis polymerization reaction are measured.
[0034] Optionally, the determination of basicity is a detection index of turbidity removal rate, which is specifically detected by orthogonal experiment, and the range analysis of the experimental results is performed.
[0035] Compared with the prior art, this application has the following beneficial effects:
[0036] 1. The flocculant polyaluminium ferric sulfate was prepared by the sulfuric acid acid dissolution method, and the influencing factors of the preparation process such as roasting temperature, sulfuric acid dosage, sulfuric acid concentration, reaction time, reaction temperature, etc. were determined, and the optimal process conditions for preparing the flocculant polyaluminium ferric sulfate by the sulfuric acid acid dissolution method were determined.
[0037] 2. The acid dissolution method of high-iron bauxite, which has a wide range of raw materials, is used to prepare a qualified polyaluminum ferric sulfate product with good wastewater treatment effect and strong self-stability. The solid product is easier to transport and store than the liquid product and is easy to promote.
[0038] 3. A composite water purifier with high turbidity removal rate can be prepared, which has lower cost and higher applicability than the traditional preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The above characteristics, features and advantages of the present invention and their implementation methods and methods will become more clearly understood in conjunction with the following description of the embodiments, which are described in detail in conjunction with the accompanying drawings. Herein, a schematic diagram is shown:
[0040] Figure 1 The present invention is a flow chart of a production process of a composite water purifier polyaluminium ferric sulfate according to an embodiment of the present invention. DETAILED DESCRIPTION
[0041] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0042] According to an embodiment of the present invention, a production process of a composite water purifier polyaluminium ferric sulfate is provided.
[0043] The present invention is further described with reference to the accompanying drawings and specific embodiments. Figure 1 As shown, according to one embodiment of the present invention, a production process of a composite water purifier polyaluminium ferric sulfate is provided, and the production process comprises the following steps:
[0044] Step 1: Analyze and pre-treat the composition of the raw material high-iron bauxite;
[0045] It should be explained that the analysis of the composition of the raw material high-iron bauxite includes the determination of iron oxide content, aluminum oxide content, calculation of effective ingredient content and determination of basicity.
[0046] Step 2: Weigh a certain amount of high-iron bauxite and roast it in a high-temperature furnace for 2 hours;
[0047] It should be explained that 20 g of high-iron bauxite was weighed and the roasting temperatures were 500°C, 600°C, 700°C, 800°C and 900°C.
[0048] Step 3: put the roasted high-iron bauxite into a container, add sulfuric acid in an amount according to the theoretical ratio of sulfuric acid dosage to raw material, add the sulfuric acid all at once and stir thoroughly;
[0049] It needs to be explained that the added sulfuric acid was grouped and compared according to different amounts and concentrations.
[0050] Step 4: placing the obtained intermediate product in a 60°C-140°C glycerol oil bath, heating and acid dissolving, adding a certain amount of catalyst and alkalizing agent for hydrolysis and polymerization for a period of time after acid dissolution;
[0051] Step 5: Turn off the oil bath, take out the container, cool and ripen to obtain the product, and measure the product.
[0052] Preferably, analyzing the composition of the raw material high-iron bauxite comprises the following steps:
[0053] S1. Determination of iron oxide content: the determination method adopts mercury-free iron determination method, and the calculation formula of iron oxide content is:
[0054] In the formula, V represents the volume value of K2Cr2O7 standard titration solution consumed during titration, C represents the accurate value of the concentration of K2Cr2O7 standard titration solution, m represents the mass of the sample, and M represents the molar mass of Fe2O3;
[0055] S2. Determination of alumina content. The calculation formula of alumina content expressed as mass fraction is:
[0056] Where V0 represents the blank test consumption Z n The volume of Cl2 standard titration solution, V represents the volume consumed by the sample n The volume of Cl2 standard titration solution, C represents Z n The concentration of Cl2 standard titration solution, m is the mass of the sample, and, is the value of the molar mass of Al2O3;
[0057] S3. Calculation of active ingredient content: X3 = X2 + 0.6348 × X1.
[0058] In the formula, X1 is the measured Fe2O3 content, X2 is the measured Al2O3 content, and 0.6348 is the coefficient for converting Fe2O3 into Al2O3;
[0059] S4. Determination of basicity. The basicity is calculated as a percentage. The calculation formula is:
[0060] Wherein, V0 is the volume of NaOH standard solution consumed in the blank test, V is the volume of NaOH standard solution consumed in the test sample, C is the concentration of NaOH standard solution, m is the mass of the sample, and M is [OH - ] is the value of the molar mass, X3 is the measured effective component content, 0.5293 is the coefficient for converting Al2O3 into Al, and 8.994 is The molar mass of .
[0061] It needs to be explained that the quality indicators of polyaluminum ferric sulfate are composed of Fe2O3 content, Al2O3 content, pH value, density, viscosity and basicity. The quality of polyaluminum ferric sulfate is judged by the measured quality indicator data.
[0062] Preferably, the high-iron bauxite weighed in step 2 is 20 g, and the roasting temperatures are 500°C, 600°C, 700°C, 800°C and 900°C.
[0063] It should be noted that sulfuric acid in the above proportion is slowly added into the fume hood and stirred, and then heated in an oil bath at 110°C for acid dissolution, and then a certain amount of alkalizer and catalyst are added for hydrolysis and polymerization, and then cooled and packed into plastic bags for sealing. After standing for about, the material is discharged, and then the turbidity removal rate of kaolin wastewater and the quality inspection of the product are determined. When the roasting temperature is 800°C, the basicity of polyaluminum ferric sulfate and the turbidity removal rate of polyaluminum ferric sulfate for kaolin wastewater are better.
[0064] Preferably, the step 1 pretreatment includes a coagulation process, and the specific steps of the coagulation process are:
[0065] A1. Simulate wastewater preparation, weigh a certain amount of kaolin, dissolve it in water, measure the turbidity of the raw water, and control its turbidity at around 340NTU;
[0066] A2. Coagulation: Take 400 ml of the experimental water sample and add 1% polyaluminium ferric sulfate flocculant. Use a program-controlled coagulation experimental agitator to conduct the experiment. Set the agitator to 300 r / min for each program. -1 Rapid stirring for 30s, 150r·min -1 Stir for 5min, 70r·min -1 Stir slowly for 10 minutes, turn off the six-joint mixer, and then let it settle for 10 minutes. Take the upper clear liquid and immediately measure the residual turbidity of the effluent.
[0067] A3. Characterization of analysis results, turbidity removal rate calculation formula:
[0068] Where T0 is the raw water turbidity, and T is the residual turbidity of the coagulated effluent.
[0069] It needs to be explained that different stirring conditions are adopted during coagulation according to the properties of various wastewaters.
[0070] Preferably, the determination of the product in step 5 includes the determination of the polyaluminium ferric sulfate morphology, the monomer state [Al+Fe] content M a Calculation: Polymeric [Al+Fe] content M b Calculation: Gel state [Al+Fe] content Mc Calculation of: M c (%) = 100% - M a -M b ,
[0071] Among them, OD0 is the absorbance value of the blank sample after boiling, OD1 is the absorbance value of the sample for 1 minute, and OD 240 OD- is the absorbance value of the sample corresponding to 240 min, and OD- is the absorbance value of the sample after boiling.
[0072] It should be explained that the absorbance value measured in the experiment is reasonably simulated, and the absorbance value corresponding to 1 minute is inferred. The mathematical simulation method is used to determine the absorbance value corresponding to 1 minute of the sample. The method is to plot the absorbance value within 3min-20min against time T, and use power function fitting to obtain the formula y=a·x b , where the coefficient a of the power function is the corresponding OD1.
[0073] Preferably, the determination of the product in step five also includes scanning electron microscopy analysis, specifically, dissolving a certain amount of high-iron bauxite raw material and flocculant product in ethanol solution, breaking them up evenly by ultrasound, and then dropping them on aluminum foil. After drying, sticking it on a sample holder, and then spraying the sample with gold, and then observing it with a scanning electron microscope.
[0074] It needs to be explained that scanning electron microscope photos of the high-iron bauxite raw material magnified 1000 times and 20,000 times show that its morphology is a layered or clustered structure, the entire shape is dispersed and disordered, the entire crystal structure presents a network structure, and is relatively densely aggregated, indicating that a polymer has been formed.
[0075] Preferably, in step 3, sulfuric acid is added at a ratio of sulfuric acid to raw material of 0.8:1, 1:1, 1.2:1, 1.4:1 and 1.6:1, and the concentration of sulfuric acid is 5 mol·L -1 , 7mol·L -1 , 9mol·L -1 , 11 mol·L -1 and 13 mol·L -1 , and determine the effect of different sulfuric acid concentrations on turbidity removal rate.
[0076] It should be explained that the amount of sulfuric acid has a great influence on the synthesis of polyaluminium ferric sulfate. The basicity decreases significantly with the increase of sulfuric acid dosage, and the turbidity removal rate increases within a certain range with the increase of sulfuric acid dosage. Therefore, an appropriate amount of sulfuric acid must be added to ensure polyaluminium ferric sulfate with a certain basicity and good flocculation effect. If too little sulfuric acid is added, Al 3+ and Fe 3+The hydrolysis reaction of the final product will be more thorough, and the basicity of the final product will be too large, resulting in the formation of unstable precipitation. If too much sulfuric acid is added, the probability of generating Al2(SO4)3 and Fe2(SO4)3 will increase. 3+ , Fe 3+ The hydrolysis tendency decreases, and the basicity of polyaluminum sulfate iron also decreases. With the increase of sulfuric acid concentration, the turbidity removal rate tends to increase, but the sulfuric acid concentration is too high, the loss is large and it has an adverse effect on the operation and environment. With the increase of sulfuric acid concentration, the Al2O3, Fe2O3 content and basicity in the solution have a downward trend. This is mainly because the solution after acid hydrolysis of high-iron bauxite is a sulfuric acid system. The solubility of aluminum sulfate and ferric sulfate in sulfuric acid is significantly lower than that in water. Aluminum sulfate and ferric sulfate form a large number of crystals and become ineffective. When the sulfuric acid concentration is 9mol·L -1 The turbidity removal rate was better, at 96.69%.
[0077] Preferably, the hydrolysis polymerization reaction time in step 4 is 60 min, 75 min, 90 min, 105 min, 120 min and 135 min, respectively, and the effects of different times on the hydrolysis polymerization reaction are measured.
[0078] It should be explained that at the beginning of the experiment, the content of dissolved aluminum oxide and iron oxide was relatively small, and the basicity was relatively high. As aluminum oxide and iron oxide continued to dissolve, the basicity decreased. After 95 minutes of reaction, the high-iron bauxite further reacted with sulfuric acid, and the basicity increased again. After 105 minutes, the basicity gradually stabilized. As the reaction time increased, the flocculation performance of the product, that is, the turbidity removal rate of kaolin simulated wastewater gradually increased. After 105 minutes of reaction, the increase in turbidity removal rate was significantly reduced. Taking all factors into consideration, the reaction time was selected to be around 105 minutes in the orthogonal design experiment.
[0079] The determination of basicity is a detection index of turbidity removal rate, which is specifically carried out through orthogonal experiments and the range analysis of the experimental results is carried out.
[0080] It should be explained that according to the results of the single factor experimental analysis, when the roasting temperature was 800°C, the three levels of the four factors of sulfuric acid dosage A, sulfuric acid concentration B, reaction time C, and reaction temperature D were selected for orthogonal design experiments. The orthogonal experiment used turbidity removal rate and basicity as detection indicators, and the experimental results were analyzed for range. The influence of each factor on the turbidity removal rate was A (3.92) > B (2.58) > C (2.47) > D (0.02). Among them, the influence of sulfuric acid dosage on product preparation was greater than that of other factors. After comprehensive analysis, the optimal combination of process conditions for this process was obtained, that is, the ratio of sulfuric acid dosage to raw materials was 1.4:1, and the sulfuric acid concentration was 8 mol·L -1, the reaction time is 100 min and the reaction temperature is 115°C.
[0081] Although the present invention has been disclosed as above with preferred embodiments, the embodiments are merely examples for the convenience of description and are not intended to limit the present invention. Those skilled in the art may make several changes and modifications without departing from the spirit and scope of the present invention. The scope of protection claimed by the present invention shall be based on the claims.
Claims
1. A production process of composite water purifier polyaluminium ferric sulfate, characterized in that: The production process includes the following steps: Step 1: Analyze and pre-treat the composition of the raw material high-iron bauxite; Step 2: Weigh a certain amount of high-iron bauxite and roast it in a high-temperature furnace for 2 hours; Step 3: put the roasted high-iron bauxite into a container, add sulfuric acid in an amount according to the theoretical ratio of sulfuric acid dosage to raw material, add the sulfuric acid all at once and stir thoroughly; Step 4: placing the obtained intermediate product in a 60°C-140°C glycerol oil bath, heating and acid dissolving, adding a certain amount of catalyst and alkalizing agent for hydrolysis and polymerization for a period of time after acid dissolution; Step 5: Turn off the oil bath, take out the container, cool and ripen to obtain the product, and measure the product.
2. The production process of a composite water purifier polyaluminium ferric sulfate according to claim 1, characterized in that: The analysis of the composition of the raw material high-iron bauxite in step 1 includes the determination of iron oxide content, the determination of aluminum oxide content, the calculation of effective ingredient content and the determination of basicity.
3. The production process of a composite water purifier polyaluminium ferric sulfate according to claim 2, characterized in that: The analysis of the composition of the raw material high-iron bauxite comprises the following steps: S1. Determination of iron oxide content: the determination method adopts mercury-free iron determination method, and the calculation formula of iron oxide content is: In the formula, V represents the volume value of K2Cr2O7 standard titration solution consumed during titration, C represents the accurate value of the concentration of K2Cr2O7 standard titration solution, m represents the mass of the sample, and M represents the molar mass of Fe2O3; S2. Determination of alumina content. The calculation formula of alumina content expressed as mass fraction is: Where V0 represents the blank test consumption Z n The volume of Cl2 standard titration solution, V represents the volume consumed by the sample n The volume of Cl2 standard titration solution, C represents Z n The concentration of the Cl2 standard titration solution, m is the mass of the sample, and M is the value of the molar mass of Al2O3; S3. Calculation of active ingredient content: X3 = X2 + 0.6348 × X1. In the formula, X1 is the measured Fe2O3 content, X2 is the measured Al2O3 content, and 0.6348 is the coefficient for converting Fe2O3 into Al2O3; S4. Determination of basicity. The basicity is calculated as a percentage. The calculation formula is: Wherein, V0 is the volume of NaOH standard solution consumed in the blank test, V is the volume of NaOH standard solution consumed in the test sample, C is the concentration of NaOH standard solution, m is the mass of the sample, and M is [OH - ] is the value of the molar mass, X3 is the measured effective component content, 0.5293 is the coefficient for converting Al2O3 into Al, and 8.994 is The molar mass of .
4. The production process of a composite water purifier polyaluminium ferric sulfate according to claim 1, characterized in that: In the step 2, 20 g of high-iron bauxite is weighed, and the roasting temperatures are 500° C., 600° C., 700° C., 800° C. and 900° C.
5. The production process of a composite water purifier polyaluminium ferric sulfate according to claim 1, characterized in that: The step 1 pretreatment includes a coagulation process, and the specific steps of the coagulation process are: A1. Simulate wastewater preparation, weigh a certain amount of kaolin, dissolve it in water, measure the turbidity of the raw water, and control its turbidity at around 340NTU; A2. Coagulation: Take 400 ml of the experimental water sample and add 1% polyaluminium ferric sulfate flocculant. Use a program-controlled coagulation experimental agitator to conduct the experiment. Set the agitator to 300 r / min for each program. -1 Rapid stirring for 30s, 150r·min -1 Stir for 5min, 70r·min -1 Stir slowly for 10 minutes, turn off the six-joint mixer, and then let it settle for 10 minutes. Take the upper clear liquid and immediately measure the residual turbidity of the effluent. A3. Characterization of analysis results, turbidity removal rate calculation formula: Where T0 is the raw water turbidity, and T is the residual turbidity of the coagulated effluent.
6. The production process of a composite water purifier polyaluminium ferric sulfate according to claim 1, characterized in that: The product is measured in step 5, including the morphology of polyaluminium ferric sulfate, the monomer state [Al+Fe] content M a Calculation: Polymeric [Al+Fe] content M b Calculation: Gel state [Al+Fe] content M c Calculation of: M c (%) = 100% - M a -M b , Among them, OD0 is the absorbance value of the blank sample after boiling, OD1 is the absorbance value of the sample for 1 minute, and OD 240 OD- is the absorbance value of the sample corresponding to 240 min, and OD- is the absorbance value of the sample after boiling.
7. The production process of a composite water purifier polyaluminium ferric sulfate according to claim 1, characterized in that: The product measurement in step five also includes scanning electron microscope analysis, specifically, a certain amount of high-iron bauxite raw material and flocculant product are dissolved in ethanol solution and evenly dispersed by ultrasound, and then dripped on aluminum foil. After drying, it is adhered to the sample holder, and then the sample is sprayed with gold and observed with a scanning electron microscope.
8. The production process of a composite water purifier polyaluminium ferric sulfate according to claim 7, characterized in that: In the step 3, sulfuric acid is added at a ratio of sulfuric acid to raw material of 0.8:1, 1:1, 1.2:1, 1.4:1 and 1.6:1, and the concentration of sulfuric acid is 5 mol·L -1 , 7mol·L -1 , 9mol·L -1 , 11 mol·L -1 and 13 mol·L -1 , and determine the effect of different sulfuric acid concentrations on turbidity removal rate.
9. The production process of a composite water purifier polyaluminium ferric sulfate according to claim 1, characterized in that: The hydrolysis polymerization reaction times in the step 4 are 60 min, 75 min, 90 min, 105 min, 120 min and 135 min respectively, and the effects of different times on the hydrolysis polymerization reaction are measured.
10. The production process of composite water purifier polyaluminium ferric sulfate according to claim 2, characterized in that: The determination of basicity is a detection index of turbidity removal rate, which is specifically detected through orthogonal experiments, and the range analysis of the experimental results is performed.